Bone scan indications in patients under 30 years of age - Manevska, Nevena; Bozinovska, Nikolina; Makazlieva, Tanja; Stojanoski, Sinisha; Majstorov, Venjamin; Miladinova, Daniela (My University, 2020)
Aim Bone scintigraphy can be a useful tool in evaluating bone disorders in young adults. Although it has a low specificity, combining planar dual phase bone scan (DPBS) and hybrid imaging (SPECT/CT), can help in detecting metabolic activity of bone lesions (BL) of various etiology. Materials & Methods Bone scan indications in young patients under 30 years were retrospectively evaluated in a two-year period at our Nuclear Medicine Department. The DPBS and afterwards SPECT/CT procedure on the region of interest was performed 3 hours after i.v application of 99mTc-MDP in dose calculated by age. Results We evaluated 65 patients (27 males, 38 females), average - 15.32±7.25y. The most frequent indication was metabolic activity of primary BL of non-malignant etiology (38/65, 58.46%), followed by primary malignant BL (12/65 patients, 18.46%). In 10 (15.38%) patients the indication was to detect bone mets due to non-bone malignancies (Malignant Melanoma, Neuroblastoma, Nephroblastoma, Medulloblastoma, Hodgkin Lymphoma, Histiocytosis). The non-malignant etiology was predominantly due to primary benign bone tumors (22/38, 57.89%) including Osteoid osteoma - 8, Fibroma Non-Ossificans - 4, Enchondroma - 1, Osteochondroma - 1, followed by Aneurysmal Bone Cyst-7, Exostosis-1. Other rare indications were trauma, sacroiliitis, rheumatologic diseases and fibrous dysplasia. In suspected malignant bone tumors histopathology revealed Osteosarcoma in 4 patients, Chondrosarcoma - 2, Ewing sarcoma - 1, Histiocytosis - 3, Malignant Lymphoma - 1, NET - 1. More than 2/3 of the patients complained of bone pain and in 23% the pain was associated with an injury. In 50/55 patients, BL presented in the appendicular skeleton, mainly in the inferior extremities. DPBS was performed in all except 9 patients (with malignancy of non-bone etiology), where indication was detecting distant mets. From 56 patients, DPBS was positive in 36.92%, while negative in the pool phase and positive only on the late phase in 27.69%. Positive both planar and SPECT/CT were detected in more than half of the patients (52.31%), while 4 patients had negative planar and positive SPECT/CT (ABC-1, Ewing - 1, Sacroiliitis - 1, Nephroblastoma - 1). Conclusion Bone scintigraphy is still a valuable nuclear method complementary to other diagnostic modalities. In young adults the main clinical indication is evaluation of primary BL of non-malignant etiology. Because of its high sensitivity, it can detect metabolic activity of BL and their turnover (osteoblastic reactions) of various etiologies (benign, malignant, traumatic, inflammatory, rheumatic) and assists in further management of the patient.